2014
DOI: 10.1093/ije/dyu112
|View full text |Cite
|
Sign up to set email alerts
|

Do the socioeconomic and hypertension gradients in rural populations of low- and middle-income countries differ by geographical region? A systematic review and meta-analysis

Abstract: We provide evidence that the association between hypertension and SES in rural populations of LMICs in Asia varies according to geographical region. This has important implications for targeting intervention strategies aimed at high-risk populations in different geographical regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 58 publications
7
48
1
1
Order By: Relevance
“…Hypertension is another glucose-independent factor in the development of endothelial dysfunction and retinopathy [27] and is an important precipitating factor for retinal ischaemia [28]. Prevalence of hypertension throughout the developing world is very variable and associations of hypertension with incomes, household assets, social class or occupation are also very variable even within a single continent [29]. In Northern Ethiopia a recent survey reported that sex-and age-adjusted mean systolic pressure was significantly higher in the urban than the rural population and also showed a positive association between systolic and diastolic pressure with both age and BMI [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is another glucose-independent factor in the development of endothelial dysfunction and retinopathy [27] and is an important precipitating factor for retinal ischaemia [28]. Prevalence of hypertension throughout the developing world is very variable and associations of hypertension with incomes, household assets, social class or occupation are also very variable even within a single continent [29]. In Northern Ethiopia a recent survey reported that sex-and age-adjusted mean systolic pressure was significantly higher in the urban than the rural population and also showed a positive association between systolic and diastolic pressure with both age and BMI [30].…”
Section: Discussionmentioning
confidence: 99%
“…China also had 5 times more hospital beds per 1,000 population than India (World Bank 2016a). To illustrate this complexity of SES-CVD association in developing countries, a recent meta-analysis showed that the association between SES and hypertension in rural populations of low- and middle-income countries in Asia may vary according to geographical regions (Busingye et al 2014). Educational status and hypertension were inversely associated in East Asia, but positively associated in South Asia.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that incidence rates of hypertension range between 3% and 18%, depending on the age, sex, ethnicity, and body size of the population studied [90]. According to recent estimates, the geographical variation in the distribution of hypertension is intensifying in several regions of the world, notably in LMICs, which now simultaneously have to grapple with the double burden of communicable diseases and NCDs despite limited health care resources [91-93]. …”
Section: Discussionmentioning
confidence: 99%